Diseases and production of promising germplasm of beans under different seeding density. - Garcés-Fiallos, Felipe Rafael (2014)
The aim was to evaluate diseases and yield components in four promising bean varieties (Phaseolus vulgaris L.) in three planting spacing. The work was carried out during the dry season of 2011, in the UTEQ, Quevedo, Ecuador. Intensity of rust (Uromyces appendiculatus) and web blight (Rhizoctonia solani) were evluated in R7 (pod formation) and R8 (pod filling) growth stages; likewise, root rot (Macrophomina phaseolina and R. solani) incidente was evaluated after harvest. Some yield components were also quantified (number of nodes, pods, grains, grains per pod and sterile pods) and grain weight. A randomized complete block (RCBD) experimental design with twelve treatments and three replications in a factorial arrangement of 4 (lines promising) x 3 (plant/m) was used. Tukey test at 5% probability of error was used for comparison between treatments means. The bean promising lines EVG 06-103 and SER-03 showed lower disease intensity. An increase in density plant population caused a higher rust intensity. Bean lines SER-08 and SER-03 showed the highest productivity, according to most yield components and grain weight. Finally, the increase in plant density promoted a significant reduction in the number of pods, grains and grains per pod per plant, contrary to the observed increase in the weight of grains.